Measurements of Validity, Factor Analysis and Reliability of the Self-Compassion Scale among School Counsellors - Mahomed, Nur Jannah Bali; Johari, Ku Suhaila Ku; Mahmud, Mohd Izwan (International Journal of Psychosocial Rehabilitation, 2020)
Self-compassion is the ability of the individual to be kind and show compassion to oneself when facing difficulties. This study aims to evaluate the validity and reliability of the Self-Compassion Scale Neff (2003) which was translated into the Malay language and an exploratory factor analysis (EFA) was conducted. A total of 115 high school counsellors were involved in this study. This instrument was subjected to face validity and content validity assessment through the CVR (content validity ration) method of Lawshe (1975). A total of 9 experts in the field and languages evaluated the instrument and the CVR results were 0.98. Through EFA, the 8th item was identified for elimination from 26 items that constitute the dimensions of self-kindness, self-judgment, common humanity, isolation, mindfulness, and over-identification. The reliability of the instrument was calculated using Cronbach’s Alpha coefficient with the result of 0.89. In conclusion, the Self-Compassion Scale in the Malay version meets the criteria of validity and reliability and can be used by researchers in the future to explore an individual’s self-compassion.